CLASSIFICATION OF DIFFERENT APPEARANCES OF TOLERANCE - Saidafzal Saidkhanbalovich Saidjalolov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article presents the essence, significance, definitions and classification of the concept of tolerance, its manifestations, and views on virtual tolerance. The importance of tolerance in maintaining peace and stability is analyzed.